(untitled) (Research, Society and Development, 2022)
Malnutrition is still a challenge for many nations, persisting among children from more socially vulnerable communities, such as rural communities. It aims to describe the nutritional status of children living in rural communities. This is an integrative literature review, in which the search for articles and sample selection will take place between September and December 2020, in which the Web of Science (WOS) databases were used. The information collected was electronically organized and compiled into a spreadsheet of the Microsoft Office Excel®version2013 program, being validated by double typing, in order to provide greater reliability. The nutritional status of malnutrition was observed in most studies, indicating that children in rural communities, with uneducated parents, in inadequate housing conditions, living in conflict zones, and socioeconomic vulnerability, are more susceptible to child food insecurity. In this sense, the relevance of well-structured and systematically effective public policies for social inclusion is highlighted, in the fight against poverty and with a focus on reducing food insecurity, aiming to promote the availability, access, and consumption of foods rich in nutrients.